MODEL ADVOKASI KEBIJAKAN BERBASIS HUKUM ADMINISTRASI NEGARA DALAM PENGUATAN PELAYANAN PUBLIK DAN PENCEGAHAN MALADMINISTRASI - Jaka Maulana; Heru Wahyudi; Ulvia Fadilah; Angga Rosidin; Nida Silvia Lestari; Yulvia Chrisdiana (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Public service is a strategic arena where governmental authority intersects with citizens' rights. Consequently, the quality of public services is strongly influenced by legal certainty, bureaucratic accountability, transparency, public participation, and the effectiveness of oversight mechanisms. This study aims to analyze the relationship between public policy advocacy, public service delivery, and administrative law, as well as to formulate an administrative law-based policy advocacy model for strengthening public services and preventing maladministration. The research employs a qualitative approach using a literature review method based on national and international scientific journal articles published between 2016 and 2026, supported by relevant laws, regulations, and official documents. The data were analyzed using thematic content analysis through the stages of data reduction, categorization, interpretation, comparison, and conceptual synthesis. The findings indicate that maladministration in public service is not solely caused by individual errors of public officials but is also influenced by regulatory weaknesses, unclear distribution of authority, ineffective procedures, limited resources, poor communication, weak oversight, and restricted public access to complaint mechanisms. Administrative law serves as the legal foundation for legitimizing, limiting, supervising, and ensuring accountability in the exercise of governmental authority, while policy advocacy functions to transform public grievances into evidence, policy agendas, and demands for institutional reform. This study proposes a six-stage policy advocacy model consisting of: (1) identification of public service problems, (2) classification of maladministration, (3) administrative law analysis, (4) formation of advocacy coalitions, (5) implementation of integrated advocacy strategies, and (6) institutionalization and monitoring of policy changes. The proposed model emphasizes that improving public service quality requires the integration of administrative capacity, legal compliance, public participation, advocacy coalitions, Ombudsman oversight, and dispute resolution mechanisms. Therefore, preventing maladministration cannot rely solely on bureaucratic innovation and digital transformation but must also be supported by strengthening citizens' rights, enhancing government transparency, and institutionalizing advocacy outcomes into regulations, service standards, complaint systems, and public service performance evaluation.